Descentralização fiscal e equidade nos serviços públicos de saúde no Brasil - Duarte, Jailson Manoel Silva (2018)
The decentralization of health services was one of the mechanisms defined in the Federal Constitution of 1988 to ensure that every citizen had access to Unified Health System (SUS). However, socioeconomic inequalities front that still exist in the Brazilian scenario, decentralization may not have resulted in a fair distribution of access to services in the various regions of the country. Based on this, the objective of this research was to analyse the relationship between fiscal decentralization and equity of access to health services in the Brazilian municipalities. We used a methodological approach consists of two steps: initially, making use of the Concentration Index, it was examined whether the equity in access to health services based on Ambulatory Production of SUS and the percentage of Hospitalizations by Cause Sensitive to Basic Care. Then a regression analysis with panel data to verify the relationship between fiscal decentralization and equity in access to health. The results showed that, even in the face of increasing public spending on health in recent years, driven by the expansion of own resources of municipalities applied in health, equity index in production SUS presented ambulatory inequality favour of the richest. In hospitalizations for causes that are sensitive to basic care, inequality was more significant in the poorest municipalities. Finally, the results presented evidence consistent with the hypothesis that the fiscal decentralization promotes to reduce inequalities in access to health in Brazilian municipalities. Therefore, the research presents empirical elements that support the arguments in favour of fiscal federalism, highlighting the importance of decentralization of public expenditure at the municipal level to enable the reduction of inequalities in health.